Development of Heritage Building-Based Modules in Rokan Regency Hulu as a Source of Learning Local History at SMA Negeri 3 Model Rambah Hilir: Pengembangan Modul Berbasis Bangunan Heritage di Kabupaten Rokan Hulu sebagai Sumber Belajar Sejarah Lokal di SMA Negeri 3 Model Rambah Hilir - Andrizal Saputra; Ahmal; Suroyo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to determine the feasibility of the Heritage building-based module in Rokan Hulu district as a source of learning local history in history subjects at SMA Negeri 3 Rambah Hilir. The use of modules in history learning is very important because students feel bored and have difficulty understanding the learning material. The methods used are qualitative and quantitative. The results of the study indicate that the developed history module is very feasible to use, and students find it easier to understand the history material given. This is evidenced by the results of media expert validation of 97,5%, material expert validation of 87,5%, small group trials of 91,5% and large group trials of 90,5%.